THE LEVEL OF EMPLOYEE PRODUCTIVITY IN THE METAL MANUFACTURING DEPARTMENT OF PT. PUPUK KALIMANTAN TIMUR - Muhammad Dixa Yusaka Zalsabila; Farapti Farapti; Abdul Rohim Tualeka; Noeroel Widajati; Putri Ayuni Alayyannur (Journal of Industrial Engineering and Operation Management (JIEOM), 2026)
Background: The level of work productivity is quite a fatal problem because its concerns the country’s economic stability. Based on data from the Badan Pusat Statistik (BPS) for 2022. Indonesia has a relatively low work productivity ranking, still around 74,4 percent, while average ASEAN productivity figure is 78,2 percent. The level of working productivity can be caused by several factors such as the work environment. One thing that can support the health of the workers is herbs.Objectives: The aim of this research is to analyze the level of employee productivity in the metal manufacturing department of fertilizer company.Method: This research was performed as an analytical observational study employing a cross-sectional design. A total of 131 individuals were chosen for the research sample using a systematic random sampling method. The data collection process includes evaluating knowledge levels using a questionnaire developed by the author, analyzing respondents' consumption habits through the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and assessing work productivity with the Individual Work Performance Questionnaire (IWPQ). This study utilized Spearman Correlation and Chi-Square methods for data analysis.Results: The results showed that there was no relationship between work productivity and level of knowledge (p=0.972) and consumption patterns (p=0.553). However, there is a relationship between the level of knowledge and consumption patterns (p=0.002).Conclusions: The conclusion of this research is that there is no relationship between the main variables studied and the level of knowledge or consumption patterns. However, the independent variables, namely the level of knowledge and consumption patterns, have a relationship with each other. The absence of relationships can be caused by various factors that have more weight, such as motivation, work environment, support from fellow colleagues and superiors, and time management.Keywords: Knowledge Level, Consumption Patterns, Work Productivity Level, Employees, Herbal Drinks.